(untitled) (ModaPalavra e-periódico, 2018)
The customized furniture industry plays a leading role in the Brazilian furniture industry, by implementing technological and formal innovations, and establishing new ways of seeing and thinking about products in the others segments of the furniture sector.The present study aims to investigate the decorative papers for the coating of manufactured boards used in the country. Starting from bibliographical research, documentary research, and field research, in addition to the ex post facto research about the experience of the practitioners. It exposes the sequence of procedures adopted in the development of the wood decors, in agreement with the academic bases of the surface design. It introduces the installed printing technologies, according to the respective raw materials. The understanding of these procedures and resources allows the improvement of the design methodologies and opens new possibilities, aiming at the evolution and expansion of this field of academic and professional performance.